1981
DOI: 10.1104/pp.67.5.1059
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Incorporation of Selenomethionine into Protein by Astragalus Polysomes

Abstract: Selenium-accumulator plants synthesize selenium compounds that differ from those produced by nonaccumulators. To determine if there are any subceilular differences between accumulators and nonaccumulators in the use of selenomethionine in vitro, polysomes from Astragais crotalriae (accumulator) and Astragaiws kntiginosis (nonaccumulator) were translated in the presence of selenomethionine. Polysomes from both species efficiently used selenomethionine in vitro during the translation process. Inasmuch as no diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

1981
1981
2012
2012

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Evidence for such a discrimination against selenocytsteine is provided by experiments which demonstrated that the cysteinyl-tRNA synthetase of the accumulator A. bisculatus was unable to use the selenium analog as a substrate (3). Crude polysome preparations from both accumulator and nonaccumulator species seem to incorporate selenomethionine into polypeptide chains during elongation (5). A third possibility, whereby the selenium content of accumulator proteins might be reduced, is enzymic removal of selenium from preformed proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence for such a discrimination against selenocytsteine is provided by experiments which demonstrated that the cysteinyl-tRNA synthetase of the accumulator A. bisculatus was unable to use the selenium analog as a substrate (3). Crude polysome preparations from both accumulator and nonaccumulator species seem to incorporate selenomethionine into polypeptide chains during elongation (5). A third possibility, whereby the selenium content of accumulator proteins might be reduced, is enzymic removal of selenium from preformed proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Selenium is present in many soil series of the arid and semiarid areas of western North America (Beath et al, 1939a(Beath et al, , 1939b(Beath et al, , 1940(Beath et al, , 1941. After absorption by plants, Se has been shown to replace S in some of the S-containing amino acids, particularly cystine (Ng and Anderson, 1978) and methionine (Eustice et al, 1981 ). The element is deficient in much of the locally grown forage of the Pacific Northwest and supplementation is required to prevent the condition known as white muscle disease in newborn lambs and calves (Carter et al, 1968(Carter et al, , 1970Muth et al, 1959).…”
mentioning
confidence: 99%
“…Gray) had 4.17 to 5.02 pmol Se/mg of protein (Brown and Shrift, 1981). The Se is incorporated into the protein molecule via the selenomethionine in the nonaccumulator species while it is deposited in structures other than protein in the accumulator species (Eustice et al, 1981 ).…”
mentioning
confidence: 99%
“…When excessive amounts of Se are taken up by plants a snow white chlorosis develops (Hurd-Karrer, 1934;Turina, 1922). Apparently the ability of seleniferous plants to tolerate large amounts of Se and at the same time avoid the toxic consequences is associated with a reduced incorporation of this element into their proteins (Brown & Shrift, 1981;Eustice, Kull & Shrift, 1981;Nigam & McConnell, 1969).…”
Section: Introductionmentioning
confidence: 99%